Bench Press and Push-up at Comparable Levels of Muscle Activity Results in Similar Strength Gains. Issue 1 (January 2015) - Calatayud, Joaquin; Borreani, Sebastien; Colado, Juan C.; Martin, Fernando; Tella, Victor; Andersen, Lars L.
Abstract : Abstract: Calatayud, J, Borreani, S, Colado, JC, Martin, F, Tella, V, and Andersen, LL. Bench press and push-up at comparable levels of muscle activity results in similar strength gains. J Strength Cond Res 29(1): 246–253, 2015—Electromyography (EMG) exercise evaluation is commonly used to measure the intensity of muscle contraction. Although researchers assume that biomechanically comparable resistance exercises with similar high EMG levels will produce similar strength gains over the long term, no studies have actually corroborated this hypothesis. This study evaluated EMG levels during 6 repetition maximum (6RM) bench press and push-up, and subsequently performed a 5-week training period where subjects were randomly divided into 3 groups (i.e., 6RM bench press group, 6RM elastic band push-up group, or control group) to evaluate muscle strength gains. Thirty university students with advanced resistance training experience participated in the 2-part study. During the training period, exercises were performed using the same loads and variables that were used during the EMG data collection. At baseline, EMG amplitude showed no significant difference between 6RM bench press and band push-up. Significant differences among the groups were found for percent change (Δ) between pretest and posttest for 6RM ( p = 0.017) and for 1 repetition maximum (1RM) ( p < 0.001). Six repetition maximum bench press group and 6RM elastic band push-up group improved their 1RM and 6RM (Δ ranging from 13.65 to 22.21) tests significantly with similar gains, whereas control group remains unchanged. Thus, when the EMG values are comparable and the same conditions are reproduced, the aforementioned exercises can provide similar muscle strength gains.